BUSINESS JUDGMENT RULE: SEBUAH PRINSIP TANGGUNG JAWAB DIREKSI ATAS KERUGIAN DALAM PENGELOLAAN BUMN (PERSERO) - Larassati Putri Syaflizar (Jurnal Privat Law, 2023)
AbstractThis article aims to determine the principles of responsibility for the directors of BUMN (Persero) based on the principles of business judgment rule in the perspective of Law Number 40 of 2007 concerning Limited Liability Companies. The research method used in this research is normative legal research. The data used are secondary data in the form of primary and secondary legal materials. The data is then processed and analyzed qualitatively. The results of the research show that the Company Law and the principles it adheres to reflect that the directors are fully responsible for the management of the Company with the protection of the principles of the business judgment rule so that if later errors or negligence of the directors are found that result in losses, the responsibility of the directors is not to the state (public). Instead, it has been transformed into (private) business responsibility based on the business judgment rule. The board of directors' responsibility can be identified by proving whether the directors' actions are honest mistakes or negliglence mistakes. If the losses caused come from actions classified as honest mistakes, the board of directors is released from their personal responsibility. However, if the loss arises from his or her actions, which are negliglence mistakes, each member of the board of directors concerned must be personally responsible.Keywords: Director; BUMN (Persero); Loss; Business Judgment Rule.AbstrakArtikel ini bertujuan untuk mengetahui prinsip tanggung jawab direksi BUMN (Persero) berdasarkan prinsip business judgment rule dalam perspektif Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif. Data yang digunakan adalah data sekunder berupa bahan hukum primer dan sekunder. Data kemudian diolah dan dianalisis secara kualitatif. Hasil dari penelitian diketahui bahwa UUPT dan prinsip-prinsip yang dianutnya mencerminkan bahwa direksi bertanggung jawab penuh terhadap pengelolaan Perseroan dengan perlindungan prinsip business judgment rule sehingga apabila di kemudian hari ditemukan kesalahan atau kelalaian direksi yang mengakibatkan kerugian, tanggung jawab direksi bukan kepada negara (publik), melainkan telah bertransformasi menjadi tanggung jawab bisnis (privat) berdasarkan business judgment rule. Untuk mengetahui sejauh mana tanggung jawab direksi, perlu dibuktikan apakah tindakan direksi tersebut merupakan honest mistakes atau negliglence mistakes. Apabila kerugian yang ditimbulkan berasal dari tindakannya yang tergolong honest mistakes, direksi lepas dari tanggung jawabnya secara pribadi. Namun, jika kerugian tersebut berasal dari tindakannya yang merupakan negliglence mistakes, setiap anggota direksi yang bersangkutan harus bertanggung jawab secara pribadi.Kata Kunci: Direksi; BUMN; Kerugian; Business Judgment Rule.